2018
DOI: 10.1097/md.0000000000011009
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for deep venous thrombosis in women with ovarian cancer

Abstract: We aim to clarify the incidence of deep venous thrombosis (DVT) before treatment in women with ovarian cancer and identify risk factors for DVT.In this prospective study, 110 women underwent venous ultrasonography before cancer treatment and D-dimer levels were measured. We investigated factors predicting DVT by logistic regression.DVT was detected in 25 of 110 women (22.7%) and pulmonary thromboembolism was coexisted in 2 women (1.8%). A total of 21 women (84.4%) with DVT were asymptomatic. D-dimer levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 22 publications
2
24
1
2
Order By: Relevance
“…Emerging studies Abbreviations: PFS progression-free survival, OS overall survival, MLR monocyte to lymphocyte ratio, NLR neutrophil to lymphocyte ratio, ALB albumin, CA125 carbohydrate antigen 125, D2 D-dimer, HR hazard ratio, CI confidence interval P values with statistical significance were denoted also suggest that a high pretreatment plasma D-dimer levels are a poor prognostic factor in EOC [8,25]. Regarding OCCC patients, in whom D-dimer levels are generally elevated and are more pronounced compared with other EOC patients, much attention has been paid to the relationship between D-dimer and venous thromboembolism [7,26]. The present study reported that a D-dimer cut-off value of 3.27 is a useful predictor of chemoresistance and can be used as an independent predictor of PFS and OS in clear cell ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies Abbreviations: PFS progression-free survival, OS overall survival, MLR monocyte to lymphocyte ratio, NLR neutrophil to lymphocyte ratio, ALB albumin, CA125 carbohydrate antigen 125, D2 D-dimer, HR hazard ratio, CI confidence interval P values with statistical significance were denoted also suggest that a high pretreatment plasma D-dimer levels are a poor prognostic factor in EOC [8,25]. Regarding OCCC patients, in whom D-dimer levels are generally elevated and are more pronounced compared with other EOC patients, much attention has been paid to the relationship between D-dimer and venous thromboembolism [7,26]. The present study reported that a D-dimer cut-off value of 3.27 is a useful predictor of chemoresistance and can be used as an independent predictor of PFS and OS in clear cell ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies also suggest that a high pretreatment plasma Ddimer levels are a poor prognostic factor in EOC [8,25] . Regarding OCCC patients, in whom D-dimer levels are generally elevated and are more pronounced compared with other EOC patients, much attention has been paid to the relationship between D-dimer and venous thromboembolism [7,26] . The present study reported that a D-dimer cut-off value of 3.27 is a useful predictor of chemoresistance and can be used as an independent predictor of PFS and OS in clear cell ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin is a signi cant prognostic factor for overall survival of ovarian cancer [6] . Plasma D-dimer levels, which are signi cantly elevated in patients with OCCC, are associated with the incidence of deep venous thrombosis [7] as well as clinical progression and poor prognosis in malignancies, including ovarian cancer [8,9] . Numerous studies have shown that elevated NLR is linked to poor prognosis among patients with solid tumors, including gynecologic cancers [10,11] , and markers of systemic in ammatory response could provide useful prognostic information of overall survival in patients with OCCC [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Emerging studies also suggest that a high pre-treatment plasma D-dimer level was recently identified as a poor prognostic factor in EOC [8,25] . Regarding OCCC patients, in which Ddimer levels are generally elevated and are more pronounced than in other EOC patients, much attention has been paid to the relationship between D-dimer and venous thromboembolism [7,26] . The present study reported D-dimer cut-off value of 3.27 is a useful predictor of chemoresistance and can be used as an independent predictor of PFS and OS in clear cell ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin was considered to be significant prognostic factors for overall survival of ovarian cancer [6] . The plasma D-dimer level, which significantly elevates in patients with OCCC, was associated with the incidence of deep venous thrombosis [7] as well as clinical progression and poor prognosis in malignancies including ovarian cancer [8,9] . Plenty of studies have shown that elevated NLR is linked to poor prognosis among patients with solid tumors including gynecologic cancers [10,11] , and markers of systemic inflammatory response could provide useful prognostic information of overall survival in patients with OCCC [12,13] .…”
Section: Introductionmentioning
confidence: 99%